Orthodontic Management of a Rare Incidence Bilateral Maxillary Canine-First Premolar Transposition Using Fixed Appliance - Samer Mereani; Amjad Alotaibi; Ahmed Bokhari (Case Reports in Dentistry)
Objective. A change in the location of two permanent teeth within the same quadrant of the dental arch is known as tooth transposition. This article illustrates the nonextraction treatment of a bilaterally complete transposition between maxillary canines and first premolars, using fixed mechanics. Material and Method. Upper and lower preadjusted, edgewise, fixed appliances with MBT prescription (0.022″×0.028″ slot size brackets) were used for the treatment. After providing room for the canine teeth, the piggyback technique was used to bring the right canine to the arch in the position of the first premolar. In the final phase of treatment, both the upper and lower arches had 0.019×0.025 stainless steel wire with Class II elastic 4 oz on the right and left sides. Result. It showed that the maxillary first premolars and canines were favorably aligned into transposed position. The upper right and left premolars occluded with the lower canines in Class I relationship and good intercuspation as well as skeletal and molar Class I relationships were maintained with a pleasant facial profile. Conclusion. The early diagnosis plays a significant role as much as considering esthetics and function factors in deciding which treatment strategy should be followed. The key to a successful and stable result is substantial treatment planning and careful orthodontic management.